DANANTARA: PILAR EKONOMI ATAU BEBAN NEGARA? - Solihin, Dadang; Arifin, Antoni Ludfi; Nugroho, Joko (FEB Universitas Sam Ratulangi Manado, 2025)
Indonesia is entering a new era in state wealth management through Danantara, a national investment institution expected to serve as a strategic instrument for economic development and improving public welfare. Danantara is designed to optimize state assets, accelerate economic development, and enhance Indonesia’s global competitiveness. This study aims to explore the potential and challenges in the implementation of Danantara as an instrument for national economic restructuring and redistribution. This research employs a descriptive qualitative approach using a literature review that includes academic references, policy documents, and international case studies. The findings indicate that Danantara holds significant potential in strengthening the national economy, improving asset management efficiency, and attracting strategic investments. However, challenges such as the potential for political intervention, governance inefficiency, and the risks of corruption and nepotism remain significant barriers. With the implementation of good governance and sustainable investment strategies, Danantara has the potential to become a key pillar in national economic development.